2018
DOI: 10.1186/s12903-018-0566-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the occlusal contact area of virtual models and actual models: a comparative in vitro study on Class I and Class II malocclusion models

Abstract: BackgroundsThe occlusal registration of virtual models taken by intraoral scanners sometimes shows patterns which seem much different from the patients’ occlusion. Therefore, this study aims to evaluate the accuracy of virtual occlusion by comparing virtual occlusal contact area with actual occlusal contact area using a plaster model in vitro.MethodsPlaster dental models, 24 sets of Class I models and 20 sets of Class II models, were divided into a Molar, Premolar, and Anterior group. The occlusal contact area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…However, due to high technical skills requirements and errors from the users, the measurements may have questionable accuracy. Hence, the 3D face scan and intraoral scan can be integrated with a CBCT scan for the facial analysis, occlusion analysis, and even digital/virtual face bow transfer and full mouth rehabilitation [22,[25][26][27][28][29][30][31][32]. The data from CBCT, intraoral scans, and facial scans can be superimposed to create a 3D "virtual patient" for better diagnosis, treatment planning, and patient outcomes [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to high technical skills requirements and errors from the users, the measurements may have questionable accuracy. Hence, the 3D face scan and intraoral scan can be integrated with a CBCT scan for the facial analysis, occlusion analysis, and even digital/virtual face bow transfer and full mouth rehabilitation [22,[25][26][27][28][29][30][31][32]. The data from CBCT, intraoral scans, and facial scans can be superimposed to create a 3D "virtual patient" for better diagnosis, treatment planning, and patient outcomes [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several new technologies have become available that can be used for occlusal assessment . T‐scan is a computerized technology that records the distribution of occlusal contacts in a time sequence, and it has been described in several studies .…”
mentioning
confidence: 99%
“…Some 3D scanning software packages can illustrate OCA, highlighting the different interocclusal distances in different colors. Although 3D scanning has recently been used to measure the OCA in plaster models, the reliability of the method was not reported . Reliability measures the degree of reproducibility and discrimination between individuals and thus relates the measurement error to the variability between subjects .…”
mentioning
confidence: 99%
“…Regarding the 3Shape system, Lee et al, determined the accuracy of the occlusal contact areas between stone casts mounted in an articulator and virtual scans obtained with the 3Shape system. The authors concluded that computerized occlusal analysis can be used for diagnostic purposes, but the software limitations have to be considered for clinical use, as well as the scanning technique which must be developed [21].…”
Section: Discussionmentioning
confidence: 99%